2009
DOI: 10.3928/1081597x-20090401-06
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NIDEK Optimized Aspheric Transition Zone Ablation Profile on Higher Order Aberrations During LASIK for Myopia

Abstract: The OATz profile may decrease the surgically induced increase of higher order aberrations, especially spherical aberration, following LASIK. However, a study with equivalent treatment groups and larger sample sizes is required for a definitive conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
1
8
0
1
Order By: Relevance
“…In our previous researches, an ablation profile for transition zone was constructed, and results showed that the transition zone played a significant role on the induced aberrations in refractive surgery [17]. Our results were in agreement with the conclusion drawn from Kosaki et al that the optimized aspheric transition zone (OATz) prole may decrease the surgically induced increase of higher order aberrations, especially spherical aberration, following LASIK [5]. Hori-Komai et al indicated that patients treated with the OATz profiles had better visual quality as measured by contrast sensitivity and also had larger effective optical zones as compared with those treated by the conventional ablation profile [18].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our previous researches, an ablation profile for transition zone was constructed, and results showed that the transition zone played a significant role on the induced aberrations in refractive surgery [17]. Our results were in agreement with the conclusion drawn from Kosaki et al that the optimized aspheric transition zone (OATz) prole may decrease the surgically induced increase of higher order aberrations, especially spherical aberration, following LASIK [5]. Hori-Komai et al indicated that patients treated with the OATz profiles had better visual quality as measured by contrast sensitivity and also had larger effective optical zones as compared with those treated by the conventional ablation profile [18].…”
Section: Discussionsupporting
confidence: 82%
“…However, the exact size, shape and the profile of transition zone have profound impact on the residual aberrations. Some researches proved that the aspheric transition zone was safe and predictable [4,5]. Arbelaez et al reported that a multidynamic aspheric transition zone was included in a laser system in order to minimize the amount of induced aberrations [6].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in HOAs has been linked to the size of the effective OZ after surgery. 31,32 The results in our study imply that custom ablation and the aberrometer we used are more sensitive to the size of the OZ. An OZ smaller than 6.0 mm can yield more HOAs than conventional treatment.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, the influence of the aspheric profiles for transition zone on higher-order aberrations was analyzed in detail in this study. Additionally, Kosaki et al indicated that the optimized aspheric transition zone ablation profile may decrease the surgically induced higher order aberrations, especially spherical aberration, following LASIK [5]. Vongthongsri et al found that LASIK with a small optical zone and high aspheric transition zone using the Nidek NAVEX system was effective, predictable, and relatively safe for correction of high myopia [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, the shape, exact size and the profile of transition zone have profound impact on the postoperative aberrations. Some researchers demonstrated that the aspheric transition zone was safe and predictable [4,5]. Our previous study conveyed that transition zone played a significant roles on the postoperative optical aberration [6].…”
Section: Introductionmentioning
confidence: 96%